Enhancing English Speaking Competence for Vocational Students: Descriptive Qualitative Analysis - Simanjuntak, Marudut Bernadtua; Sutrisno, Sutrisno; Lumingkewas, Martin Steven (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research explores the critical need for speaking skills and competencies in English in the context of vocational education. Through a comprehensive exploration of language skills, linguistics and literature, human resource management, and the role of learning organizations, this study provides an in-depth understanding of the important role of literacy in English in vocational education. The findings reveal that English proficiency is not just an advantage but an absolute necessity for vocational students in today's increasingly connected world. English serves as a gateway to a wide range of global information, collaboration with international peers, and participation in a wider professional network. Effective communication in English is now a prerequisite in the job market, with recruiters in various industries looking for candidates who have strong English-speaking skills. In addition, the study emphasizes that the linguistic and literary dimensions in English proficiency not only deepen communication skills but also increase cultural awareness. By understanding the nuances of language, vocational students can navigate a diverse professional environment with cultural sensitivities, which is an invaluable trait in the global world of work. Learner organizations play an important role as champions of change, influencing curriculum development and resource allocation to support English language education for vocational students